(3OjhGf GHf GdeYJR (B/s - (3WQGO, eLjOs; (3GHf GdeYJR, YHO Gddg Hf eMeO GdeYJR HGddg Hf GdeJhcd,s 247-296 (3g`(B.s ((3HjQhJ (B:s (3OGQ GdcJGH GdYQHj,s, 1995)
(3OjhGf(B.s
Keywords: (3GdTYQ GdYQHjs -- (3GdYUQ GdYHGSj GdKGfj, (B846-954s